African Historical Archaeologies
VII, 408 p. 82 illus.
Keywords: This volume explores the range of interactions between the historical sources and archaeology that are available on the African continent. The contributions, written by a range of experts on different aspects of African archaeology, present the underlying issues such as: - The conflict and collaboration in the foundation of modern Africa; - African trading communities maintaining their independence from Europe; - The impacts of the Atlantic slave trade. This represents the first consideration of historical archaeology over the African continent as a whole and therefore provides an important review for African archaeologists and historians. This seminal volume also explores Africa's place in global systems of thought and economic development for historical archaeologists and historians alike.